Research Status and Application Prospect of Epigenetic Regulation of BDNF Gene Expression in Chronic Pain - Wei Xiang; Na-Wang Li (International Journal of Pain Management, 2019)
The rise of epigenetics provides a new idea for studying the regulation of chronic pain-related genes and synaptic plasticity. External environmental stimuli can regulate BDNF genes through different epigenetic modifications. The epigenetic changes of the BDNF gene can affect the expression of its mRNA and protein and participate in the development of chronic pain. By reviewing the literature, this paper reviews the mechanism of epigenetic regulation of brain-derived neurotrophic factor (BDNF) in chronic pain, which provides some new directions and targets for the treatment of chronic pain.
Keywords: chronic pain